Angiomatosis of the breast: a clinicopathological and immunophenotypical characterisation of seven cases. Issue 9 (14th May 2019) - Ginter, Paula S; McIntire, Patrick J; Irshaid, Lina; Liu, Yi-Fang; Shin, Sandra J
Abstract : Aims: Mammary angiomatosis is a rare, benign vascular lesion that morphologically mimics low-grade angiosarcoma (LGAS). To date, only occasional reports of this entity have been published, none of which included analysis by immunohistochemistry. The purpose of this study was to further characterise mammary angiomatosis by clinical, histological, and immunohistochemical means while emphasising distinguishing features from LGAS. Methods: Seven cases of primary mammary angiomatosis were evaluated. For one patient, a subsequent recurrence was also evaluated. Results: All patients were female with a median age at presentation of 51 years (range: 19–58 years). The most common clinical presentation was that of a palpable abnormality or mass (5/8) and the median primary tumour size was 3.1 cm (range: 2–9 cm). Of the six patients with follow-up, one developed a recurrence 6 years after initial presentation. Histologically, all cases were composed of variably sized ectatic, thin-walled vessels lined by flat normochromic endothelium diffusely infiltrating mammary stroma. Where present, lesional vessels infiltrated between and around terminal duct lobular units but not into individual intralobular stroma. Most cases (6/8) showed a combination of lymphatic-appearing and haemangiomatous-appearing vessels. Lymphatic-appearing vessels were D2-40 positive in all but one case. D2-40 was negative or weak in haemangiomatous-appearing vessels. All lesional vessels were CD31 positive. Ki-67 indices were <1% in all but one case (5%). Conclusions: Mammary angiomatosis is a rare vascular lesion that shares clinical, morphological and immunohistochemical features with LGAS; however, certain key traits make the distinction possible.